Reduction of Greenhouse Gas Emissions through Community-Scale Pyrolysis Technology in Bogor City and its Financial Feasibility - Salwa Nur Allysa; Pini Wijayanti (Brawijaya University, 2023)
Population growth affects the generation of plastic waste and could potentially increase greenhouse gas (GHG) emissions through the burning process. This has become a severe problem as it contributes to global warming. Therefore, plastic waste management is required, for instance, by using pyrolysis technology on a community scale. Such a project will reduce plastic waste and GHG emissions by processing plastic into valuable products. This study aims (1) to estimate potential GHG emissions before the project implementation, (2) to estimate potential GHG emissions reduction after the project implementation, and (3) to assess both potential revenue and profit of pyrolysis products. This study employs SNI 19-3694-1994 method to estimate household waste generated, the clean development mechanism (CDM) method to estimate GHGs emissions reduction, and the profit comparison method (PCM) to asses both revenue and profit of pyrolysis products. The results show that GHG emissions before the project will be 3.69 t CO2e in 2021 and could increase to 4.61 t CO2e in 2030. Potential GHG emissions reduction depends on the fuel types to heat the reactor. Only electric pyrolysis will reduce GHG emissions by up to 0.46 t CO2e (13%) annually. This project is not financially feasible because operational costs (15,772,779 IDR) exceed the annual revenue (1,014,000 IDR).Keywords: CDM, climate change, GHG emission, plastic waste, pyrolysis